Preparation method of silver phosphate-containing hydrogel film for photodegradation of high-salt pollutants

By forming a liquid film on a nonwoven fabric with an aqueous solution of silver phosphate and sodium alginate and crosslinking of oxalic acid to form a hydrogel film, the problem that photocatalyst powder is not easy to reuse and difficult to recover the supported catalyst is solved, and efficient Degradation of high-salt pollutants and reusable silver phosphate.

CN119406434APending Publication Date: 2025-02-11TIANJIN POLYTECHNIC UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411437567.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing photocatalyst powder is not easy to be reused, the supported catalyst is difficult to recover and regenerate, and the ionic crosslinked alginate is not salt-resistant, etc.

Method used

A mixture of silver phosphate and sodium alginate is used as the cast film liquid to form a liquid film on the non-woven fabric, and a hydrogel film is formed by cross-linking of oxalic acid. The film is used to degrade high-salt contaminants under ultraviolet or visible light and to recover silver phosphate powder by dissolving sodium carbonate.

Benefits of technology

The silver phosphate photocatalyst is reusable and efficiently recovered, and the stability and swelling resistance of the hydrogel film in a high-salt environment are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406434A_ABST
    Figure CN119406434A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a silver phosphate-containing hydrogel film for photodegradation of high-salt pollutants. The preparation method comprises the following steps: reacting silver nitrate with trisodium phosphate to obtain silver phosphate, preparing a mixture aqueous solution of silver phosphate and sodium alginate as a membrane casting solution, coating a non-woven fabric with the membrane casting solution under a winding transmission device, and crosslinking with an oxalic acid aqueous solution to obtain the silver phosphate-containing hydrogel membrane for photodegradation of high-salt pollutants. The hydrogel film is arranged in a fixed frame, the hydrogel film and the fixed frame are soaked in an aqueous solution of pollutants containing high-concentration inorganic salt, and the pollutants are degraded under irradiation of ultraviolet light or visible light. The preparation method comprises the following steps: dissolving a hydrogel film with reduced catalytic performance after repeated use with a sodium carbonate aqueous solution, carrying out centrifugal separation, washing with deionized water, and drying to obtain recovered silver phosphate powder, thereby re-preparing the hydrogel film containing silver phosphate for photodegradation of high-salt pollutants. The preparation method is simple, industrialization is easy, the photocatalyst silver phosphate can be recycled and regenerated, and good application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing a hydrogel film containing silver phosphate for photodegrading high-salt pollutants, and belongs to the field of functional materials and advanced oxidation water treatment. Background Art

[0002] With the continuous development of industry, water pollution is becoming more and more serious. Organic waste is a major cause of water pollution. There are many types of organic pollutants in water bodies, with complex components and toxicity, which are extremely harmful to the environment and human body. The printing and dyeing industry has developed rapidly, and a large amount of printing and dyeing wastewater containing salt and organic pollutants is generated every year. A large amount of salt-containing wastewater infiltrates into the soil, which will cause soil salinization, soil compaction and other problems. High-salt wastewater refers to wastewater with a salt content of more than 1g / L. Traditional physical desalination technology has a relatively mature application system in industry, but it has defects such as secondary pollution, equipment corrosion, easy scaling, and high cost of later maintenance.

[0003] Photocatalytic degradation is a process that uses highly active free radicals generated by radiation and photocatalysts in the reaction system to degrade pollutants into inorganic substances through processes such as addition, substitution, and electron transfer between free radicals and organic pollutants. The essence of photocatalytic reaction is redox reaction. When semiconductor photocatalytic materials are irradiated by light, they absorb light energy. Once the energy exceeds its threshold, the material will be excited, thereby generating photogenerated electrons (e - ) and holes (h + ), electrons and holes migrate to the surface of the catalytic material, where electrons are captured by dissolved oxygen to form superoxide radicals (·O 2- ), while the holes will be adsorbed on the catalyst surface, oxidizing water and hydroxide ions into hydroxyl radicals (·OH). Both of these substances have strong oxidizing properties, thereby oxidizing pollutants on the surface of the material into CO2 and H2O. Photocatalytic technology has broad prospects in the treatment of industrial wastewater due to its advantages of being green, clean, and economical. Traditional commercial catalysts represented by P25-TiO2 are widely used in various industries [J. Applied Chemical Industry, 2008, (05): 472-474]. However, nano-semiconductor catalysts have problems such as difficulty in recycling and secondary pollution, making them difficult to be widely used. Therefore, it is particularly important to design a composite catalyst of photocatalytic semiconductor@carrier.

[0004] Silver phosphate is a newly developed visible light photocatalyst with good visible light photocatalytic activity. Silver phosphate exhibits excellent catalytic performance for levofloxacin lactate [J. Journal of the Chinese Ceramic Society, 2012, 40(12): 1796-1801]. Wang et al. prepared silver phosphate photocatalyst using a two-step precipitation method, i.e., preparing silver carbonate by precipitation, and then preparing silver phosphate product by exchanging silver carbonate with phosphate ions. The degradation efficiency of methyl orange by the silver phosphate catalyst obtained by the two-step method is much higher than that of the silver phosphate catalyst obtained by one-step precipitation. The decolorization efficiency of methyl orange can reach 98% in a shorter time and at a lower light intensity. However, the stability of the silver phosphate photocatalyst is poor. As the number of cycles increases, the removal rate of methyl orange is only 12.85% after six cycles [J. New Chemical Materials, 2014, 42 (05): 108-110]. Luo et al. prepared silver phosphate photocatalyst by precipitation method. The silver phosphate photocatalyst catalyzed the degradation of pollutants such as crystal violet (CV), methylene blue (MB) and methyl orange (MO) under simulated light conditions. The results showed that silver phosphate had a strong catalytic effect on these three pollutants. However, it could not completely photocatalyze the dye into CO2 and H2O. This is attributed to the fact that in the photodegradation of aqueous dye solutions, due to the Ag in silver phosphate + It is rapidly deactivated by photoreduction to metallic Ag [J. Applied Surface Science, 2014, 319: 332-338]. Yan Lin et al. synthesized a new photocatalyst silver phosphate @NC. The results showed that after coupling with NC, the charge separation efficiency and photostability of silver phosphate were significantly improved. The silver phosphate @NC composite material has excellent photocatalytic degradation efficiency for norfloxacin, diclofenac and phenol. The photocatalyst showed excellent catalytic activity for the degradation of norfloxacin, diclofenac and phenol, reaching 100% removal rate at visible light irradiation of 5, 8 and 12 min, respectively. The photocatalyst can effectively use natural light for environmental treatment. [J. Advanced Functional Materials, 2020, 30(38): 2002918].

[0005] In the traditional wastewater treatment process, photocatalysts are usually used in the form of suspended systems because the suspended particles have a large surface area. However, the separation of suspended photocatalysts in wastewater will inevitably increase operating costs and cause secondary pollution, thus greatly limiting its practical application. However, many substrates used to fix photocatalysts have some defects, such as the easy shedding of inorganic carrier photocatalyst coatings, poor compatibility of polymer-supported catalysts and easy degradation and loss of strength of polymers, poor carrier flexibility and inconvenience in use, etc. Alginate has attracted attention as a photocatalyst carrier or precursor. Sodium alginate can be dissolved in water at room temperature to form a hydrosol, and its linear long molecular chain is similar to the molecular chain of pure polyuronic acid. Its most important property is that it can react with calcium salts to form gels. Even at room temperature and physiological pH, sodium alginate aqueous solution will undergo gelation reaction when encountering divalent (except magnesium ions) and multivalent metal ions to form ion-crosslinked alginate hydrogels. TiO2 nanoparticles can be well dispersed and fixed in porous calcium alginate fibers to form photocatalytically active materials [Water Research, 2012, 46:1858-872]. Zhao Kongyin et al. mixed the photocatalyst and sodium alginate to prepare a casting solution, scraped it on a glass plate with a scraping rod, and obtained a photocatalyst / alginate composite film through metal ion crosslinking [201310424400.0]. The ion crosslinking agent in the alginate hydrogel does not degrade when irradiated, and although the alginate macromolecules degrade, they can still form a hydrogel with a strength similar to that before degradation, which greatly improves the reusability of the membrane. The preparation process of the composite hydrogel catalytic membrane is simple, low in cost, and no pollutants are generated during the preparation process. It is green and environmentally friendly. In addition, the composite hydrogel catalytic membrane is treated by soaking in a strong metal ion complexing agent, and the photocatalyst can be recovered by simple precipitation separation. However, the calcium alginate hydrogel membrane prepared by calcium ion crosslinking has poor stability in high salt solution and is easy to swell.

[0006] Xie Wenbin et al. prepared a green hydrogel membrane (CMCS-OA-NaAlg) by cross-linking two natural macromolecules, sodium alginate (NaAlg) and carboxymethyl chitosan (CMCS), with oxalic acid (OA) non-metallic ions. The membrane exhibits excellent anti-swelling and good anti-fouling properties at high salt concentrations. The membrane can achieve better dye / salt separation [Chinese Chemical Letters, 2022, 33, 1951-1955]. Pérez-Madrigal Maria M et al. prepared a membrane with sodium alginate and oxalic acid as carriers, which has better elasticity and good potential as a synergistic anticancer drug carrier. The cohesion of oxalic acid-based gels is the result of the coexistence of multiple ion complexes, including oxalic acid, sodium alginate and sodium ions, which stabilize the system and keep all interacting species together. Subbaiah Muthu Prabhu et al. synthesized alginate-oxalate-zirconium (Alg-Ox-Zr), alginate-malonic acid-zirconium and alginate-succinic acid-zirconium complexes using oxalic acid, malonic acid and succinic acid as media, and studied their fluoride removal performance.

[0007] The present invention reports a method for preparing a hydrogel film containing silver phosphate for photodegrading high-salt pollutants. Silver phosphate is obtained by reacting silver nitrate with trisodium phosphate, and an aqueous solution of a mixture of silver phosphate and sodium alginate is prepared as a casting solution. The casting solution is coated on a non-woven fabric under a winding transmission device, and then cross-linked with an oxalic acid aqueous solution to obtain a hydrogel film containing silver phosphate for photodegrading high-salt pollutants. The hydrogel film is loaded into a fixed frame, immersed in an aqueous solution containing pollutants with a high concentration of inorganic salts, and irradiated under ultraviolet light or visible light to degrade the pollutants. The hydrogel film whose catalytic performance has been reduced after repeated use is dissolved with an aqueous sodium carbonate solution, centrifuged and washed with deionized water, and dried to obtain a recovered silver phosphate powder, thereby re-preparing a hydrogel film containing silver phosphate for photodegrading high-salt pollutants. The preparation method of the present invention is simple and easy to industrialize, and the photocatalyst silver phosphate can be recycled and regenerated, and has good application prospects. Summary of the invention

[0008] In view of the shortcomings of the prior art, the technical problems that the present invention intends to solve are that the photocatalyst powder is not easy to reuse, the loaded catalyst is difficult to recycle and regenerate, and the ion-crosslinked alginate is not salt-tolerant. The technical solution to the problems of the present invention is to provide a method for preparing a hydrogel film containing silver phosphate for photodegrading high-salt pollutants.

[0009] The present invention provides a method for preparing a hydrogel film containing silver phosphate for photodegrading high-salt pollutants, which is characterized by comprising the following steps: A sodium phosphate trihydrate aqueous solution and a silver nitrate aqueous solution were prepared with deionized water, and the sodium phosphate trihydrate aqueous solution was added dropwise into the silver nitrate aqueous solution under light-shielding and stirring conditions. After the reaction was completed, the precipitate was obtained by centrifugation and washed with deionized water for 3 times, and then dried to obtain silver phosphate powder; A mixture of 0.5% to 5% sodium alginate and 0.1% to 3% silver phosphate powder obtained in step a) is prepared as a casting solution, and the mixture is defoamed and then used for later use; Prepare an oxalic acid aqueous solution with a mass percentage concentration of 1% to 10% as a coagulation bath; A nonwoven fabric with one side hydrophilic and the other side hydrophobic from Beijing Dayuan Nonwoven Co., Ltd. is selected as a carrier, and the casting solution obtained in step b) is coated on the nonwoven fabric with the hydrophilic side by a scraper under a winding transmission device to form a liquid film on the nonwoven fabric, and then the nonwoven fabric coated with the film solution is immersed in the coagulation bath obtained in step c), and the hydroxyl groups on the alginate are cross-linked with oxalic acid to generate a hydrogel, and after sufficient cross-linking, the oxalic acid on the surface is washed off with deionized water to obtain a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants, and the hydrogel film is wound together for standby use; Cutting the hydrogel film containing silver phosphate for photodegrading high-salt pollutants obtained in step d) and placing it in a fixed frame, immersing the hydrogel film together with the frame in a mixed aqueous solution containing 1% to 30% by mass of inorganic salts and 0.01% to 1% by mass of organic pollutants, and irradiating the solution under ultraviolet light or visible light for 0.5 to 5 hours, so that the degradation rate of the organic pollutants reaches 80% to 100%; The hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants, whose catalytic performance has been reduced after repeated use, is dissolved in an aqueous sodium carbonate solution, centrifuged and the precipitate is washed with deionized water, and then dried to obtain the recovered silver phosphate powder, thereby re-preparing the hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants.

[0010] The inorganic salt of the present invention is any one of sodium chloride, potassium chloride, magnesium chloride, sodium sulfate and magnesium sulfate or a mixture of two or more thereof; the organic pollutant is any one of methyl orange, tetracycline, bisphenol A and dibutyl phthalate or a mixture of two or more thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0012] Figure 1This is a flow chart of the preparation and application of a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants provided in Example 1; Figure 2 is a scanning electron microscope photograph of a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants provided in Example 1; Figure 3 This is a graph showing the catalytic degradation of methyl orange with different salt contents by a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants under ultraviolet light provided in Example 1; The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0013] The preparation and application flow chart of the present invention is shown in Figure 1 Specific embodiments of the present invention are described below, but the present invention is not limited to the embodiments. Example

[0014] A sodium phosphate trihydrate aqueous solution and a silver nitrate aqueous solution were prepared with deionized water, and the sodium phosphate trihydrate aqueous solution was added dropwise into the silver nitrate aqueous solution under light-shielding and stirring conditions. After the reaction was completed, the precipitate was obtained by centrifugation and washed with deionized water for 3 times, and then dried to obtain silver phosphate powder; A mixture of 2.5% sodium alginate and 0.5% silver phosphate powder obtained in step a) is prepared as a casting solution, and the mixture is defoamed and then used for later use; Prepare an aqueous solution of oxalic acid with a mass percentage concentration of 3% as a coagulation bath; A nonwoven fabric with one side hydrophilic and the other side hydrophobic from Beijing Dayuan Nonwoven Co., Ltd. is selected as a carrier. Under a winding transmission device, the casting solution obtained in step b) is coated on the nonwoven fabric on the hydrophilic side with a scraper to form a liquid film on the nonwoven fabric. The nonwoven fabric coated with the film solution is then immersed in the coagulation bath obtained in step c), and the hydroxyl groups on the alginate are cross-linked with oxalic acid to form a hydrogel. After sufficient cross-linking, the oxalic acid on the surface is washed off with deionized water to obtain a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants. The hydrogel film is wound together for use. The scanning electron microscope photomicrograph of the hydrogel film containing silver phosphate for photodegradation of high-salt pollutants is shown in FIG. Figure 2 ; Cutting the hydrogel film containing silver phosphate for photodegrading high-salt pollutants obtained in step d) and placing it in a fixed frame, immersing the hydrogel film together with the frame in a mixed aqueous solution containing 1% by mass concentration of sodium chloride and 0.001% by mass concentration of methyl orange, and irradiating it under ultraviolet light for 0.2 hours, the degradation rate of methyl orange reaches 60%; Figure 3This is the catalytic degradation diagram of the hydrogel film of silver phosphate photodegradation of high-salt pollutants to methyl orange with different salt contents under ultraviolet light. It can be seen that the addition of inorganic salt sodium chloride has no effect on the photocatalytic degradation performance of the film; The hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants, whose catalytic performance has been reduced after repeated use, is dissolved in an aqueous sodium carbonate solution, centrifuged and the precipitate is washed with deionized water, and then dried to obtain the recovered silver phosphate powder, thereby re-preparing the hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants. Example

[0015] A sodium phosphate trihydrate aqueous solution and a silver nitrate aqueous solution were prepared with deionized water, and the sodium phosphate trihydrate aqueous solution was added dropwise into the silver nitrate aqueous solution under light-shielding and stirring conditions. After the reaction was completed, the precipitate was obtained by centrifugation and washed with deionized water for 3 times, and then dried to obtain silver phosphate powder; A mixture of 5% sodium alginate and 3% silver phosphate powder obtained in step a) is prepared as a casting solution, and the mixture is defoamed and set aside; Prepare an aqueous solution of oxalic acid with a mass percentage concentration of 10% as a coagulation bath; A nonwoven fabric with one side hydrophilic and the other side hydrophobic from Beijing Dayuan Nonwoven Co., Ltd. is selected as a carrier, and the casting solution obtained in step b) is coated on the nonwoven fabric with the hydrophilic side by a scraper under a winding transmission device to form a liquid film on the nonwoven fabric, and then the nonwoven fabric coated with the film solution is immersed in the coagulation bath obtained in step c), and the hydroxyl groups on the alginate are cross-linked with oxalic acid to generate a hydrogel, and after sufficient cross-linking, the oxalic acid on the surface is washed off with deionized water to obtain a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants, and the hydrogel film is wound together for standby use; Cutting the hydrogel film containing silver phosphate for photodegrading high-salt pollutants obtained in step d) and placing it in a fixed frame, immersing the hydrogel film together with the frame in a mixed aqueous solution containing 30% by mass concentration of potassium chloride and 1% by mass concentration of tetracycline, and irradiating it under ultraviolet light for 0.5 hours, the degradation rate of tetracycline reaches 80%; The hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants, whose catalytic performance has been reduced after repeated use, is dissolved in an aqueous sodium carbonate solution, centrifuged and the precipitate is washed with deionized water, and then dried to obtain the recovered silver phosphate powder, thereby re-preparing the hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants. Example

[0016] A sodium phosphate trihydrate aqueous solution and a silver nitrate aqueous solution were prepared with deionized water, and the sodium phosphate trihydrate aqueous solution was added dropwise into the silver nitrate aqueous solution under light-shielding and stirring conditions. After the reaction was completed, the precipitate was obtained by centrifugation and washed with deionized water for 3 times, and then dried to obtain silver phosphate powder; A mixture of 2.5% sodium alginate and 1% silver phosphate powder obtained in step a) is prepared as a casting solution, and the mixture is defoamed and set aside; Prepare an aqueous solution of oxalic acid with a mass percentage concentration of 5% as a coagulation bath; A nonwoven fabric with one side hydrophilic and the other side hydrophobic from Beijing Dayuan Nonwoven Co., Ltd. is selected as a carrier, and the casting solution obtained in step b) is coated on the nonwoven fabric with the hydrophilic side by a scraper under a winding transmission device to form a liquid film on the nonwoven fabric, and then the nonwoven fabric coated with the film solution is immersed in the coagulation bath obtained in step c), and the hydroxyl groups on the alginate are cross-linked with oxalic acid to generate a hydrogel, and after sufficient cross-linking, the oxalic acid on the surface is washed off with deionized water to obtain a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants, and the hydrogel film is wound together for standby use; Cutting the hydrogel film containing silver phosphate for photodegrading high-salt pollutants obtained in step d) and placing it in a fixed frame, immersing the hydrogel film together with the frame in a mixed aqueous solution containing 0.1% by mass of magnesium chloride and 0.1% by mass of bisphenol A, and irradiating it under ultraviolet light for 2 hours, the degradation rate of bisphenol A reaches 99%; The hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants, whose catalytic performance has been reduced after repeated use, is dissolved in an aqueous sodium carbonate solution, centrifuged and the precipitate is washed with deionized water, and then dried to obtain the recovered silver phosphate powder, thereby re-preparing the hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants. Example

[0017] A sodium phosphate trihydrate aqueous solution and a silver nitrate aqueous solution were prepared with deionized water, and the sodium phosphate trihydrate aqueous solution was added dropwise into the silver nitrate aqueous solution under light-shielding and stirring conditions. After the reaction was completed, the precipitate was obtained by centrifugation and washed with deionized water for 3 times, and then dried to obtain silver phosphate powder; A mixture of 2.5% sodium alginate and 2% silver phosphate powder obtained in step a) is prepared as a casting solution, and the mixture is defoamed and set aside; Prepare an aqueous solution of oxalic acid with a mass percentage concentration of 6% as a coagulation bath; A nonwoven fabric with one side hydrophilic and the other side hydrophobic from Beijing Dayuan Nonwoven Co., Ltd. is selected as a carrier, and the casting solution obtained in step b) is coated on the nonwoven fabric with the hydrophilic side by a scraper under a winding transmission device to form a liquid film on the nonwoven fabric, and then the nonwoven fabric coated with the film solution is immersed in the coagulation bath obtained in step c), and the hydroxyl groups on the alginate are cross-linked with oxalic acid to generate a hydrogel, and after sufficient cross-linking, the oxalic acid on the surface is washed off with deionized water to obtain a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants, and the hydrogel film is wound together for standby use; Cutting the hydrogel film containing silver phosphate for photodegrading high-salt pollutants obtained in step d) and placing it in a fixed frame, immersing the hydrogel film together with the frame in a mixed aqueous solution containing 4% by mass of sodium sulfate and 0.02% by mass of dibutyl phthalate, and irradiating the solution under visible light for 5 hours, so that the degradation rate of dibutyl phthalate reaches 90%; The hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants, whose catalytic performance has been reduced after repeated use, is dissolved in an aqueous sodium carbonate solution, centrifuged and the precipitate is washed with deionized water, and then dried to obtain the recovered silver phosphate powder, thereby re-preparing the hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants. Example

[0018] A sodium phosphate trihydrate aqueous solution and a silver nitrate aqueous solution were prepared with deionized water, and the sodium phosphate trihydrate aqueous solution was added dropwise into the silver nitrate aqueous solution under light-shielding and stirring conditions. After the reaction was completed, the precipitate was obtained by centrifugation and washed with deionized water for 3 times, and then dried to obtain silver phosphate powder; A mixture of 0.5% sodium alginate and 0.1% silver phosphate powder obtained in step a) is prepared as a casting solution, and the mixture is defoamed and set aside; Prepare an aqueous solution of oxalic acid with a mass percentage concentration of 1% as a coagulation bath; A nonwoven fabric with one side hydrophilic and the other side hydrophobic from Beijing Dayuan Nonwoven Co., Ltd. is selected as a carrier, and the casting solution obtained in step b) is coated on the nonwoven fabric with the hydrophilic side by a scraper under a winding transmission device to form a liquid film on the nonwoven fabric, and then the nonwoven fabric coated with the film solution is immersed in the coagulation bath obtained in step c), and the hydroxyl groups on the alginate are cross-linked with oxalic acid to generate a hydrogel, and after sufficient cross-linking, the oxalic acid on the surface is washed off with deionized water to obtain a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants, and the hydrogel film is wound together for standby use; Cutting the hydrogel film containing silver phosphate for photodegrading high-salt pollutants obtained in step d) and placing it in a fixed frame, immersing the hydrogel film together with the frame in a mixed aqueous solution containing 0.1% by mass of magnesium sulfate and 0.001% by mass of methyl orange and bisphenol A, and irradiating the solution under ultraviolet light for 5 hours, the degradation rates of methyl orange and bisphenol A both reached 90%; The hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants, whose catalytic performance has been reduced after repeated use, is dissolved in an aqueous sodium carbonate solution, centrifuged and the precipitate is washed with deionized water, and then dried to obtain the recovered silver phosphate powder, thereby re-preparing the hydrogel membrane containing silver phosphate for photodegrading high-salt pollutants.

Claims

1. A method for preparing a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants, characterized in that The following steps are involved: a) preparing a trisodium phosphate aqueous solution and a silver nitrate aqueous solution with deionized water respectively, and dripping the trisodium phosphate aqueous solution into the silver nitrate aqueous solution dropwise under light-shielding and stirring conditions, after the reaction is completed, centrifuging to obtain a precipitate, washing it 3 times with deionized water, and drying it to obtain a silver phosphate powder; b) preparing a mixture of sodium alginate with a mass percentage concentration of 0.5% to 5% and the silver phosphate powder obtained in step a) with a mass percentage concentration of 0.1% to 3% as a casting solution, and defoaming it for later use; c) preparing an aqueous solution of oxalic acid with a mass percentage concentration of 1% to 10% as a coagulation bath; d) selecting a non-woven fabric with one side hydrophilic and the other side hydrophobic from Beijing Dayuan Nonwoven Co., Ltd. as a carrier, coating the casting solution obtained in step b) on the non-woven fabric with the hydrophilic side with a scraper under a winding transmission device to form a liquid film on the non-woven fabric, and then immersing the non-woven fabric coated with the film solution in the coagulation bath obtained in step c), cross-linking the hydroxyl groups on the alginate with oxalic acid to generate a hydrogel, and after sufficient cross-linking, washing away the oxalic acid on the surface with deionized water to obtain a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants, and winding the hydrogel film together for standby use; e) cutting the hydrogel film containing silver phosphate for photodegrading high-salt pollutants obtained in step d) and placing it in a fixed frame, immersing the hydrogel film together with the frame in a mixed aqueous solution containing 0.1% to 30% by mass of inorganic salts and 0.001% to 1% by mass of organic pollutants, and irradiating the solution under ultraviolet light or visible light for 0.2 to 5 hours, so that the degradation rate of the organic pollutants reaches 60% to 100%; f) dissolving the hydrogel film containing silver phosphate for photodegrading high-salt pollutants whose catalytic performance has been reduced after repeated use with an aqueous sodium carbonate solution, centrifuging and washing the precipitate with deionized water, and drying to obtain recovered silver phosphate powder, thereby re-preparing the hydrogel film containing silver phosphate for photodegrading high-salt pollutants.

2. The method for preparing a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants as claimed in claim 1, characterized in that The inorganic salt is any one of sodium chloride, potassium chloride, magnesium chloride, sodium sulfate and magnesium sulfate, or a mixture of two or more thereof.

3. The method for preparing a hydrogel film containing silver phosphate for photodegradation of high-salt pollutants as claimed in claim 1, characterized in that The organic pollutant is any one of methyl orange, tetracycline, bisphenol A and dibutyl phthalate or a mixture of two or more thereof.

Citation Information

Patent Citations

  • Alginate-based composite hydrogel catalytic membrane of renewable catalyst and preparation method thereof

    CN103464217A